Sistem Informasi Pemesanan Tiket Bus Online Berbasis Website Pada Po. Haryanto - Vita Ariska; Tiara Aulia Nur Fadilla; Tinuk Agustin (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The rapid development of technology makes companies flock to compete in using technology. Especially in the field of transportation, the company uses the technology that is currently developing, namely the website. This website can be used as a media campaign and also an application to support the company, especially this bus company. PO. Haryanto is a company engaged in the field of transportation services. In carrying out its activities, this company still uses a manual service system. In this study designing a website-based online bus ticket booking information system, it is hoped that with this information system, it can facilitate online bus ticket booking services for prospective passengers. The method used in this study uses data collection techniques such as observation and literature study methods. This application uses the Java programming language and MySQL as the database. While system design is done using UML (Unified Modeling Language). The results obtained from the system created include being able to order bus tickets online based on a website so that it becomes more efficient and does not require much time.